Fault-Controlled Magma Ascent Recorded in the Central Series of the Rum Layered Intrusion, NW Scotland. (9th October 2020) - Troll, V R; Mattsson, T; Upton, B G J; Emeleus, C H; Donaldson, C H; Meyer, R; Weis, F; Dahrén, B; Heimdal, T H
Abstract: The Palaeogene layered ultrabasic intrusion of the Isle of Rum forms the hearth of the Rum Igneous Centre in NW-Scotland. The regional Long Loch Fault, which is widely held to represent the feeder system to the layered magma reservoir, dissects the intrusion and is marked by extensive ultrabasic breccias of various types. Here we explore the connection between the layered ultrabasic cumulate rocks and breccias of central Rum that characterize the fault zone (the 'Central Series') and evaluate their relationship with the Long Loch Fault system. We show that fault splays in the Central Series define a transtensional graben above the Long Loch Fault into which portions of the layered units subsided and collapsed to form the extensive breccias of central Rum. The destabilization of the cumulate pile was aided by intrusion of Ca-rich ultrabasic magmas along the faults, fractures and existing bedding planes, creating a widespread network of veins and dykelets that provided a further means of disintegration and block detachment. Enrichment in LREE and compositional zoning in intra cumulate interstices suggest that the collapsed cumulates were infiltrated by relatively evolved plagioclase-rich melt, which led to extensive re-crystallization of interstices. Clinopyroxene compositions in Ca-rich gabbro and feldspathic peridotite veins suggest that the intruding magma was also relatively water-rich, and that pyroxene crystallized dominantly below the current level of exposure. We propose that the Long Loch Fault opened and closed repeatedly to furnish the Rum volcano with a pulsing magma conduit. When the conduit was shut, pressure built up in the underlying plumbing system, but was released during renewed fault movements to permit dense and often crystal-rich ultrabasic magmas to ascend rapidly from depth. These spread laterally on arrival in the shallow Rum magma reservoir, supplying repetitive recharges of crystal-rich magma to assemble the rhythmic layering of the Rum layered intrusion.